Afforestation policies, planning and progress - Mather, Alexander S. (Alexander Smith) (London Belhaven Press, 1993)
Introduction / Alexander Mather -- Afforestation in Britain / Alexander Mather -- Afforestation in the Republic of Ireland / Desmond Gillmor -- Afforestation in Denmark / Kr. Marius Jensen -- Hungary / B. Keresztesi -- Afforestation policy and practice in Spain / Helen J. Groome -- Afforestation in Algeria / Philip Stewart -- Afforestation in China / Vaclav Smil -- Forest plantations in Chile: a successful model? / Antonio Lara, Thomas T. Veblen -- New Zealand: afforestation policy in eras of state regulation and de-regulation / M. M. Roche, R. B. LeHeron -- Reafforestation in Australia / G. T. McDonald -- Modern development of afforestation in Japan: process and results / Yoshihisa Fujita -- Afforestation: the United States / Michael Williams -- Review / Alexander Mather.
Includes bibliographical references and index.
Keywords: Afforestation -- Europe